ANALGETICS-ANTIPYRETICS IN PEDIATRICIAN’S PRACTICE: THE POINT OF VIEW OF CLINICAL PHARMACOLOGIST - G.G. Ketova (Вопросы современной педиатрии, 2009)
The article discusses on of the main problems of pediatrics — the problem of hyperthermia in children and administration of antipyretics. A pathogenesis of a fever and «point of attack» of antipyretics, data on effectiveness and adverse events of this group of medications are presented.Key words: children, fever, antipyretics, indications.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(6):135-138)